O Estabelecimento de Vínculos entre Cuidadores e Crianças no Contexto das Instituições de Acolhimento: um Estudo Teórico - Medeiros, Blenda Carine Dantas De (2018)
Abstract This article focuses on a theoretical discussion about the work of the resident caregivers, who work in home-based care institutions taking care of children and teenagers. The article aims to analyze the normative documents on which are based the practices of those professionals in relation to those children and their families, and to study the daily experiences of the caregivers. Thus, we did a brief theoretical review on the policies of reception for children and teenagers in Brazil, followed by an analysis of the academic productions that point out aspects regarding the relations established in these reception spaces, based on bibliographical research made in the Parthenon and BDTD, with the following descriptors: “mãe social”, “mães sociais”, “cuidador* resident*” and “acolhimento”, in different combinations and varying the search fields. The reading of the articles, thesis and dissertations allowed us to discuss some issues related to the work of resident caregivers and the establishment of bond with children and adolescents hosted, highlighting the tensions experienced by these professionals, which can lead to illness due to their job. With more questions than clarifications, the urgency to look at the professional and personal identity of the resident caregivers, who professionally assume a constant affective reference point and a daily follow-up of children and adolescents in a foster care situation, is assured.